Maternal Diet during Pregnancy Induces Gene Expression and DNA Methylation Changes in Fetal Tissues in Sheep - Lan, Xianyong; Cretney, Evan C.; Kropp, Jenna; Khateeb, Karam; Berg, Mary; Peñagaricano, Francisco; Magness, Ronald; Radunz, Amy; Khatib, Hasan (Frontiers in Genetics, 2013)
Studies in rats and mice have established that maternal nutrition induces epigenetic modifications, sometimes permanently, that alter gene expression in the fetus, which in turn leads to phenotypic changes. However, limited data is available on the influence of maternal diet on epigenetic modifications and gene expression in sheep. Therefore, the objectives of this study were to investigate the impact of different maternal dietary energy sources on the expression of imprinted genes in fetuses in sheep. Ewes were naturally bred to a single sire and from d 67 ± 3 of gestation until necropsy (d 130 ± 1), they were fed one of three diets of alfalfa haylage (HY; fiber), corn (CN; starch), or dried corn distiller’s grains (DG; fiber plus protein plus fat). A total of 26 fetuses were removed from the dams and longissimus dorsi, semitendinosus, perirenal adipose depot, and subcutaneous adipose depot tissues were collected for expression and DNA methylation analyses. Expression analysis of nine imprinted genes and three DNA methylatransferase (DNMTs) genes showed significant effects of the different maternal diets on the expression of these genes. The methylation levels of CpG islands of both IGF2R and H19 were higher in HY and DG than CN fetuses in both males and females. This result is consistent with the low amino acid content of the CN diet, a source of methyl group donors, compared to HY and DG diets. Thus, results of this study provide evidence of association between maternal nutrition during pregnancy and transcriptomic and epigenomic alterations of imprinted genes and DNMTs in the fetal tissues.